2020
DOI: 10.3389/fimmu.2020.02100
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in Pro- and Anti-tumor Activity of Neutrophils: Shifting the Balance

Abstract: Over the last decades, cancer immunotherapies such as checkpoint blockade and adoptive T cell transfer have been a game changer in many aspects and have improved the treatment for various malignancies considerably. Despite the clinical success of harnessing the adaptive immunity to combat the tumor, the benefits of immunotherapy are still limited to a subset of patients and cancer types. In recent years, neutrophils, the most abundant circulating leukocytes, have emerged as promising targets for anti-cancer th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 250 publications
(292 reference statements)
5
66
0
1
Order By: Relevance
“…7f ). These results are consistent with a pro-tumor role of IL-17 and possibly neutrophils in aggressive niches, as has been described for N2 neutrophils and/or granulocytic myeloid-derived suppressor cells (G-MDSCs) 50 , 51 .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…7f ). These results are consistent with a pro-tumor role of IL-17 and possibly neutrophils in aggressive niches, as has been described for N2 neutrophils and/or granulocytic myeloid-derived suppressor cells (G-MDSCs) 50 , 51 .…”
Section: Resultssupporting
confidence: 90%
“…In particular, we identified that S100A8+ neutrophils specifically infiltrated aggressive niches, which also displayed increased IL-17 signaling. Tumor-associated neutrophils, or TANs, have been reported to play dual roles in the tumor microenvironment, including in breast cancer 51 , 89 91 . The functional role of TANs in DCIS, which have been shown to increase compared to normal tissue, is not known, but may be similarly double-sided 19 , 92 .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, when compared with a population of animals identically treated with isotype control (pooled from multiple cohorts), animals treated with anti-IL-17 showed delayed latency to a palpable tumor (Fig 7F). These results are consistent with a pro-tumor role of IL-17 and possibly neutrophils in aggressive niches, as has been described for N2 neutrophils and/or granulocytic myeloid derived suppressor cells (G-MDSCs) (Furumaya et al, 2020;Ostrand-Rosenberg and Fenselau, 2018).…”
Section: Inhibition Of Granulocyte Recruitment Reduces Aggressive Niche Formation and Delays Tumor Progressionsupporting
confidence: 90%
“…In particular, we identi ed that S100A8+ neutrophils speci cally in ltrated aggressive niches, which also displayed increased IL-17 signaling. Tumor-associated neutrophils, or TANs, have been reported to play dual roles in the tumor microenvironment, including in breast cancer (Fridlender et al, 2009;Furumaya et al, 2020;Jaillon et al, 2020;Mishalian et al, 2013). The functional role of TANs in DCIS, which have been shown to increase compared to normal tissue, is not known, but may be similarly double-sided (Gil Del Alcazar et al, 2017;Nelson et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A substantial amount of preclinical and clinical studies has indicated that tumor-associated myeloid cells, predominantly tumorassociated macrophages (TAMs), neutrophils, and myeloidderived suppressor cells (MDSCs), sustain an immunosuppressive tumor microenvironment, which is particularly refractory to both T cell trafficking and antitumor T cell functions (4,(129)(130)(131)(132)(133)(134). Extensive research in this field has additionally concluded that the specific targeting and/or elimination of this myeloid-driven immunosuppressive program can render the natural, induced, and engineered immunological responses against tumors more concrete and effective (135)(136)(137). In line with the above, here we first provide proof-of-principle evidence of this notion using the Mouse Mammary Tumor Virus Polyoma Middle-T antigen (MMTV-PyMT) mouse model of breast carcinoma, which successfully recapitulates human breast cancer progression (138).…”
Section: The Cancer Cell Dissemination Trajectory As An Immunosuppressive Nichementioning
confidence: 99%